The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/nu15020386
|View full text |Cite
|
Sign up to set email alerts
|

Is Citicoline Effective in Preventing and Slowing Down Dementia?—A Systematic Review and a Meta-Analysis

Abstract: Background: Cognitive impairment is a staggering personal and societal burden; accordingly, there is a strong interest in potential strategies for its prevention and treatment. Nutritional supplements have been extensively investigated, and citicoline seems to be a promising agent; its role in clinical practice, however, has not been established. We systematically reviewed studies on the effect of citicoline on cognitive performance. Methods: We searched the PubMed and Cochrane Library databases for articles p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
(70 reference statements)
0
3
0
1
Order By: Relevance
“…In the last two decades, a large number of studies have investigated the effects of citicoline supplementation in modulating cognitive functions in several neurological diseases, like Alzheimer's disease, Parkinson's disease, MCI and vascular cognitive impairment [15,[17][18][19][20][21][22]. More recently, a meta-analytic study including 6 studies on citicoline supplementation in patients with Alzheimer's disease, MCI and post-stroke dementia published between 2010 and 2022, suggested that citicoline has a positive effect on cognitive functions, although the general quality of the included studies was poor [23]. Studies in experimental animals have shown that citicoline modulates both adrenergic and dopaminergic metabolism in the brain [24]; moreover, it seems to enhance cerebral metabolism, and to exert neuroprotective actions in animals and humans [18,19,25].…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, a large number of studies have investigated the effects of citicoline supplementation in modulating cognitive functions in several neurological diseases, like Alzheimer's disease, Parkinson's disease, MCI and vascular cognitive impairment [15,[17][18][19][20][21][22]. More recently, a meta-analytic study including 6 studies on citicoline supplementation in patients with Alzheimer's disease, MCI and post-stroke dementia published between 2010 and 2022, suggested that citicoline has a positive effect on cognitive functions, although the general quality of the included studies was poor [23]. Studies in experimental animals have shown that citicoline modulates both adrenergic and dopaminergic metabolism in the brain [24]; moreover, it seems to enhance cerebral metabolism, and to exert neuroprotective actions in animals and humans [18,19,25].…”
Section: Discussionmentioning
confidence: 99%
“…Given that pharmacology and nutrition have some points in common, we will also discuss some data we have found regarding the relationship between nutrition and AD. Various nutrients and nutraceuticals have been linked to improvements in cognition and other psychological aspects related to AD ( Guzman-Martinez et al, 2021 ; Abduljawad et al, 2022 ; Mahnashi et al, 2022 ; Xu Lou et al, 2023 ) Some examples include Gingko Biloba ( Liao et al, 2020 ), Melissa Officinalis ( Noguchi-Shinohara et al, 2020 ; Noguchi-Shinohara et al, 2022 ), Ginseng ( Ahmad et al, 2023 ), anti-inflammatory fatty acids ( Albrahim, 2020 ), medium-chain fatty acids ( Juby et al, 2022 ), ketone bodies ( Avgerinos et al, 2020a ), saffron ( Avgerinos et al, 2020b ; Talebi et al, 2021 ), fenugreek seed ( Foroumandi et al, 2023 ), genistein ( Viña et al, 2022 ), sodium oligomannate ( Xiao et al, 2021 ), anthocyanin ( Suresh et al, 2022 ), microbiota and probiotics ( Den et al, 2020 ; Maitre et al, 2021 ; Liu et al, 2022 ; Naomi et al, 2022 ), benfotiamine ( Gibson et al, 2020 ), omega-3 fatty acids ( Canhada et al, 2018 ; Jernerén et al, 2019 ), resveratrol ( Gu et al, 2021 ; Buglio et al, 2022 ; Fang et al, 2022 ; Tosatti et al, 2022 ), melatonin ( Tseng et al, 2022 ), citicoline ( Bonvicini et al, 2023 ), folic acid, vitamin B12 ( Chen et al, 2021 ), vitamins and minerals ( Mccleery et al, 2018 ; Karthika et al, 2022 ), selenium ( Pereira et al, 2022 ), vitamin D ( Jia et al, 2019 ), and mangosteen ( Muangpaisan et al, 2022 ). However, some studies do not support the efficacy of certain nutrients ( Zhu et al, 2018 ; Thancharoen et al, 2019 ; Araya-Quintanilla et al, 2020 ; Burckhardt et al, 2020 ; Du et al, 2020 ; Prabhakar et al, 2020 ; Shim et al, 2021 ; Tofiq et al, 2021 ; Takada et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with these data, glaucoma therapy has now fully embraced neuroprotective molecules, such as citicoline [7,51,52], that have been used in Alzheimer's disease therapy [53,54], and other neurotrophins have been studied in glaucoma research [55][56][57].…”
Section: Glaucoma and Neurodegenerationmentioning
confidence: 99%